A Comprehensive Psychometric Examination of the Lesbian, Gay, and Bisexual Knowledge and Attitudes Scale for Heterosexuals (LGB-KASH). Issue 8 (3rd July 2019) - Raju, Dheeraj; Beck, Lisa; Azuero, Andres; Azuero, Casey; Vance, David; Allen, Rebecca
ABSTRACT: Heterosexual attitudes toward individuals with other sexual orientations and identities, such as lesbian, gay, bisexual, transgender, intersex, asexual, etc. (LGBTQIA+), have been conceptualized as multidimensional and wide-ranging. With the objective of measuring these attitudes, Worthington and colleagues developed the Lesbian, Gay, and Bisexual Knowledge and Attitudes Scale for Heterosexuals (LGB-KASH). In this article, 540 college students were administered the LGB-KASH; these data were examined for their psychometric properties of the instrument using a sequential approach. The first step included descriptive analysis, including internal consistency measures and association rules, followed by the evaluation of dimension structure with factor analysis (confirmatory/exploratory), and, finally, item analysis using non-parametric (Mokken scale analysis) and parametric approaches (item response theory). Specific to the LGB-KASH factor structure, the current structure was not supported by these data; however, alternative subsets of items that could be used to revise the original instrument to obtain a more psychometrically sound measure are suggested.